MENTHOL AS ANESTHESIC FOR DOURADO (Salminus brasiliensis) - de PÁDUA, Santiago Benites [UNESP]; de PIETRO, Pamela Souza; Iglessias-Filho, Paulo Sérgio; Ishikawa, Márcia Mayumi; Hisano, Hamilton (My University, 2010)
Different levels of menthol as an anesthetic for dourado (Salminus brasiliensis) were evaluated in this study. Fish (n=32) with average weight of 194.13 ± 9.06 g and total mean length of 25.30 ± 0.90 cm were separated in four groups composed of 8 individuals. Each group was submitted to different menthol concentrations: 60, 90, 120 and 150 mg L-1. Total induction time was analyzed by polynomial regression and other parameters by Tukey´s test. All experimental fish exposed to different concentrations of menthol reached deep anesthesia stage without mortality. It was observed a negative linear effect (P<0.05) for total induction time. The longest recovery time (172.60 s) was observed for dourado treated with 120 mg. L-1, which differed (P<0.05) from the 90 mg.L-1 treatment (122.03 s). All levels evaluated in this study were safe and effective. A concentration of 60 mg L-1 for dourado is suggested based on lower cost and adequate induction and recovery time responses.
MENTOL COMO ANESTÉSICO PARA DOURADO (Salminus brasiliensis)
Keywords: Alternative anesthetic; freshwater fish; Mentha spp; native species